Cancer prevention strategies in different countries: Qualitative and quantitative differences. Issue 2 (January 2015) - Facchiano, Antonio
Abstract: In this presentation quantitative as well as qualitative analyses are reported regarding the communication strategies in the field of cancer prevention in the English-speaking world as compared to Italian-speaking world. The quantitative analyses were based on the occurrence of specific keywords in the global literature accessible via internet as well as on the chromatic -complexity investigated in a total of 1400 images. Such images refer to the "prevention" field and were taken from internet English-domains and Italian-domains. This study represents a preliminary report regarding a novel linguistic approach to assess the efficacy of cancer prevention strategies. The conclusions indicate significant and relevant quantitative differences between communication strategies having language differences.